Role of Instrument-assisted Soft Tissue Mobilisation in Text Neck Syndrome: A Quasi-experimental Study - Amita Aggarwal; Anuj Pawan Lahoti; Tushar J Palekar (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Text Neck Syndrome occurs due to sustained Forward Head Posture (FHP) when smartphones are used constantly without any breaks for more than five hours and with improper posture. Long-term untreated text neck can cause inflammation of the neck’s ligaments, muscles, and nerves, leading to chronic arthritic changes. Literature provides studies evaluating the effects of physical or manual therapy, but there is a lack of studies investigating the effects of Instrument-assisted Soft Tissue Mobilisation (IASTM) treatment in individuals with text neck syndrome. Aim: To determine the added effect of IASTM on text neck syndrome. Materials and Methods: This quasi-experimental study was conducted at Department of Physiotherapy, Dr. D.Y. Patil College of Physiotherapy, Pune, Maharashtra, India, from August 2022 to December 2022. A total of 22 subjects, with a mean age of 21.58±1.18 years, participated in the study. The subjects were then divided into two treatment groups (n=11 each). The experimental group (Group-A) received stretching, strengthening exercises with IASTM, while the control group (Group-B) received only conventional physical therapy (stretching and strengthening). The treatment was delivered for a twoweek period. The data were analysed using MedCalc statistical software version 20.210. Significance was set at a p-value less than 0.05. For within-group analysis, Wilcoxon’s signed-rank or paired t-test was used depending on the normality distribution, and for between-group comparisons, Mann-Whitney tests were used for skewed variables. Results: The pain severity (p-value=0.0063) and neck disability (p-value=0.0008) were significantly lower in the IASTM group than the control group. Additionally, the Craniovertebral Angle (CVA) (p-value=0.0001) significantly increased with IASTM (Group-A) compared to the control group. Conclusion: The study concluded that IASTM and conventional therapy are individually effective in improving pain, disability, and FHP in text neck syndrome. However, adding IASTM to routine physical therapy showed statistically more significant results compared to physical therapy alone in reducing neck pain, disability, and FHP.